The cortisol awakening response: Association with training load in endurance runners - Anderson, T.; Lane, A. R.; Hackney, A. C. (International Journal of Sports Physiology and Performance, 2018)
The cortisol awakening response (CAR) is commonly used as a marker of psychological stress; however, it is unknown whether CAR is affected by regular physical-exercise-induced stress. Purpose: To assess the relationship between training load and CAR. Methods: Recreational endurance athletes were recruited from local running clubs. Subjects (n?=?15) completed training logs for 2 wk, with various training loads, including psychometric analysis (Recovery-Stress Questionnaire for Athletes). Subjects provided saliva samples each day immediately after waking and 30 min postwaking. Samples were analyzed for cortisol concentration via enzyme-linked immunosorbent assay and subsequently were analyzed for CAR and CAR%. Daily training load was calculated and analyzed as training impulse. Simple linear regression was used to assess the relationship between CAR and training impulse. Results: CAR (r2=.352, P=.025) and CAR% (r2=.373, P=.012) both showed a significant negative relationship with training load. Conclusions: These results suggest that CAR is affected by regular exercise training loads in recreational athletes. It is recommended that future CAR research control for fitness level and exercise training load in physically active populations.